Emotional Analysis of the Main Character in Leiden by Dwi Nur Rahmawati: Implications for Literature Education in the Merdeka Curriculum - Saripudin, Agus; Fikri, Fikri; Gunaika, Raka; Angelia, Tassya (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This study examines the emotional dynamics of the main character in Dwi Nur Rahmawati's Leiden and analyzes how these emotions can inform literature teaching within the Merdeka Curriculum. Employing a descriptive mixed-methods design, the research integrates qualitative literary psychology analysis with quantitative frequency mapping. Data were collected through systematic reading, identification of emotional expressions, structured recording, and coding of 76 emotional quotations from the novel. Analysis followed Miles, Huberman, and Saldaña's interactive model to classify emotion types, examine narrative contexts, identify patterns, and interpret pedagogical relevance. The findings revealed three significant patterns. First, sadness emerged as the dominant emotion (18.4%), followed by love and fear (14.5% each) and guilt (11.8%), indicating the protagonist's psychological vulnerability characteristic of adolescent development. Second, nonverbal behavior (39.5%) and author narration (35.5%) appeared more frequently than dialogue (25%), demonstrating a